Validation of the Body Scan®, a new device to detect small fiber neuropathy by assessment of the sudomotor function: agreement with the Sudoscan® - Riveline, Jean-Pierre; Mallone, Roberto; Tiercelin, Clarisse; Yaker, Fetta; Alexandre-Heymann, Laure; Khelifaoui, Lysa; Travert, Florence; Fertichon, Claire; Julla, Jean-Baptiste; Vidal-Trecan, Tiphaine; Potier, Louis; Gautier, Jean-Francois; et al. (Frontiers in Neurology, 2023)
Background Sudomotor dysfunction is one of the earliest manifestations of small fiber neuropathy (SFN), reflecting the alteration of sympathetic C fiber innervation of the sweat glands. Among other techniques, such innervation can be assessed by measuring electrochemical skin conductance (ESC) in microsiemens (μS). In this study, ESC was measured at the feet to detect distal SFN. For this objective, the performance of a new device, the Body Scan® (Withings, France), intended for home use, was compared with that of a reference device, the Sudoscan® (Impeto Medical, France), which requires a hospital setting. Methods In patients with diabetes with or without neuropathy or non-diabetic patients with lower-limb neuropathy, the diagnostic performance of the Body Scan® measurement was assessed by calculating its sensitivity (Se) and specificity (Sp) to detect at least moderate SFN (Se70 and Sp70), defined by a value of feet ESC ≤ 70 μS and > 50 μS on the Sudoscan® measure, or severe SFN (Se50 and Sp50), defined by a value of feet ESC ≤ 50 μS on the Sudoscan® measure. The agreement between the two devices was assessed with the analysis of Bland–Altman plots, mean absolute error (MAE), and root mean squared error (RMSE) calculations. The repeatability of the measurements was also compared between the two devices. Results A total of 147 patients (52% men, mean age 59 years old, 76% diabetic) were included in the analysis. The sensitivity and specificity to detect at least moderate or severe SFN were: Se70 = 0.91 ([0.83, 0.96]), Sp70 = 0.97 ([0.88, 0.99]), Se50 = 0.91 ([0.80, 0.98]), and Sp50 = 0.99 ([0.94, 1]), respectively. The bias and 95% limits of agreement were 1.5 [−5.4, 8.4]. The MAE was 2.9 and the RMSE 3.8. The intra-sample variability was 2.0 for the Body Scan® and 2.3 for the Sudoscan®. Conclusion The ESC measurements provided by the Body Scan® were in almost perfect agreement with those provided by the reference device, the Sudoscan®, which validates the accuracy of the Body Scan® for the detection of SFN. By enabling simple, rapid, and autonomous use by the patient at home, this new technique will facilitate screening and monitoring of SFN in daily practice. Clinical trial registration ClinicalTrials.gov, identifier NCT05178459.